Perbandingan Tingkat Motivasi Mahasiswa yang Menempuh Kuliah Konvensional dengan Collaborative Learning - Herman Herman; Titi Savitri P; Widyandana Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2014)
Background: Collaborative learning is a learning method which centered on students’ learning process. Although many theories and research results showed that interactive lecture is better than conventional lecture, but in fact, only few lecturers use the interactive method in teaching and learning process. Literature stated that using conventional method in teaching and learning process does not motivate students to learn more while using the other one (interactive lecture) will enhance students’ motivation. Collaborative learning is one of interactive lecture method. Based on the facts mentioned above, the researcher wants to compare students’ motivation who participate in conventional method and those who participate in collaborative learning method.Method: This was a quantitative research with experimental approach, used posttest only with control group design. This research measured students’ learning motivation by using Motivated Strategies for Learning Questionnaire (MSLQ). Subjects for the research were the second semester students of Public Health Scince of Tadulako University which divided into two groups randomly. Data were analyzed by Mann-Whitney test method.Results: There were a distinct disparity in students’ learning motivation after following learning process with conventional and collaborative learning method. Students who followed collaborative learning had higher motivation than students who followed conventional lecture.Conclusion: Collaborative learning improves students’ learning motivation toward the nutrient topic on Public Health Sciences.